Trade policies and agricultural exports of Ecuador. Period 2010-2016 - Gallegos Santillán, Doris Nataly (2019)
Objective: To study the commercial policies applied in Ecuador, during the period 2010 - 2016 to determine the incidence of these policies on the performance of agricultural exports. Method: The analytical - synthetic method was used based on primary, secondary and theoretical sources, which allowed analyzing the performance of exports and trade policies. Results: In this period, the trade balance of traditional products and non-oil products registered an upward trend due to the price but in certain areas it decreased due to the world trade situation. Conclusions: The foreign trade policies applied in Ecuador from 2010 to 2016 have not been effective in expanding the markets for agricultural products and for a productive reactivation since exports depend largely on endogenous and exogenous factors that prevent the achievement of sustained economic growth.